Does the quality of pain relief after major surgery influence the risk of postoperative complications? A prospective observational study - Christine Kubulus; Marcus Komann; Markus Paxian; Ann-Kristin Schubert; Daniel Schwarzkopf; Norman Rose; Winfried Meissner; Ursula Marschall; Johannes Dreiling; Carolin Fleischmann-Struzek; Thomas Volk (PLoS ONE, 2025)
Objectives Effective postoperative acute pain management continues to be a challenge. It remains uncertain whether poorly controlled postoperative pain influences the risk of postoperative complications. Therefore, we aimed to investigate whether indicators of poor pain control increase the likelihood of cardiac, pulmonary, infectious, thromboembolic, and surgical complications, as well as of prolonged use of analgesics. Methods This prospective observational study combines treatment data from the German net-ra registry and claims data from the second-largest public health insurer BARMER (Mar 1, 2021-Mar 31, 2022). A total of 539 adult inpatients who had undergone major surgery and received planned postoperative care from acute pain services were analyzed. Adjusted binary logistic regression models were fitted to compare patients with inadequately (NRS > 3) and adequately controlled pain, with (NRS > 6) and without pain peaks, and with slow or rapid pain recovery (median split of the time to sustained adequate pain control NRS ≤ 3) with regard to the risk of postoperative complications and prolonged use of analgesics as a proxy of chronic postoperative pain. Results Patients with inadequately controlled pain within the first three postoperative days had more than twice the risk of complications (adjOR 2.56; 95% CI 1.43–4.80, p = 0.002), as did patients with slow pain recovery (adjOR 2.21; 95% CI 1.35–3.64, p = 0.002). No significant effect could be observed for pain peaks (adjOR 1.27; 95% CI 0.64 to 2.42, P = 0.478). Inadequate pain control did not significantly affect prolonged use of analgesics (adjOR 1.87; 95% CI 0.98–3.72, p = 0.064), nor did pain peaks or recovery speed show any influence. Discussion We observed a clear link between postoperative quality of pain control and complications, along with a trend towards prolonged use of analgesics. Therefore, postoperative acute pain should be regularly assessed and minimized until resolved. Further research into patient- and procedure-specific factors is essential to reduce adverse pain-related outcomes.